The Economic Theory of Regulation: Evidence from the Uniform CPA Examination. - Young, S. David (The Accounting Review, 1988)
The economic theory of regulation suggests that occupational licensing laws are enacted and administered to advance the interests of licensed practitioners. For example, grading standards on licensing examinations could be altered to protect incumbent practitioners from new competitors. This possibility is investigated with time series data of Uniform CPA Examination results for California and Illinois. The results indicate that when the exam was graded by the individual states, exam failure rates increased with downturns in economic activity (as measured by unemployment rates). However, the evidence shows no statistical relation between failure rates and economic activity in the years after each of the states adopted the AICPA's Advisory Grading Service.